2005
DOI: 10.1016/j.drugalcdep.2005.01.009
|View full text |Cite
|
Sign up to set email alerts
|

fMRI response to spatial working memory in adolescents with comorbid marijuana and alcohol use disorders

Abstract: Alcohol and marijuana use are prevalent in adolescence, yet the neural impact of concomitant use remains unclear. We previously demonstrated functional magnetic resonance imaging (fMRI) response to spatial working memory (SWM) among teens with alcohol use disorders (AUD) compared to controls, and predicted that adolescents with marijuana and alcohol use disorders would show additional abnormalities.Participants were three groups of 15−17-year-olds: 19 non-abusing controls, 15 AUD teens with limited exposure to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
130
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 112 publications
(138 citation statements)
references
References 51 publications
6
130
1
1
Order By: Relevance
“…In contrast, our previous work revealed increased SWM response in this region among heavy alcohol-and marijuana-using teens who had been abstinent an average of just 8 days (Schweinsburg et al, 2005b). Kanayama and colleagues (Kanayama et al, 2004) also observed greater dorsolateral prefrontal response among adult heavy marijuana users on a similar SWM task 6-36 h after marijuana use.…”
Section: Discussioncontrasting
confidence: 54%
See 4 more Smart Citations
“…In contrast, our previous work revealed increased SWM response in this region among heavy alcohol-and marijuana-using teens who had been abstinent an average of just 8 days (Schweinsburg et al, 2005b). Kanayama and colleagues (Kanayama et al, 2004) also observed greater dorsolateral prefrontal response among adult heavy marijuana users on a similar SWM task 6-36 h after marijuana use.…”
Section: Discussioncontrasting
confidence: 54%
“…Research on parietal functioning during working memory among individuals with substance use disorders has been somewhat inconsistent. Using the same SWM task, we previously failed to observe parietal abnormalities among adolescent users of alcohol and marijuana (Schweinsburg et al, 2005b), though teens with alcohol use disorders alone showed increased posterior parietal brain response compared with controls (Tapert et al, 2004) despite similar task performance between groups. Greater fMRI activation in posterior parietal cortex has also been observed during SWM among adult marijuana users (Kanayama et al, 2004) as well as during verbal working memory among adolescent marijuana users experiencing nicotine withdrawal (Jacobsen et al, 2007).…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations